Edukasi Pertolongan Pertama dalam Kondisi Gawat Darurat sebagai Upaya Peningkatan Keterampilan Mahasiswa - Wasis Widodo; Novia Wulansari; Firmansyah Firmansyah; Rochmayanti Rochmayanti; Jajat Sudrajat; Devanda Faiq Albyn (Yayasan Inspirasi El Burhani, 2026)
Introduction: When something unexpected happens and requires immediate assistance, it's called an emergency, and that's when first aid comes into play. Therefore, pre-hospital care should be a competency for nursing and midwifery students at the Annisa Health and Business Institute. To prepare for developing emergency situations, efforts are needed to increase knowledge and hone skills in various emergency situations. Objective: To enable participants to apply their knowledge on campus and off campus, this educational activity and practical stimulation will hone their abilities and skills. Method: This implementation was carried out on September 19, 2025, with 65 nursing and midwifery student respondents. The method was through a community service project focused on (PPGD). The method was to provide participants with an understanding of the material. This community service project utilized debate, role-playing, and simulation techniques. Planned improvements in student confidence, practice, and abilities related to BLS, CPR, burn evaluation, choking, and patient evacuation. Results: All prospective nursing and midwifery students gained practical skills and knowledge from the activity, as well as their creativity, encouraging them to be brave, and most importantly, by providing real-world situations so they have a proactive mindset when facing accidents. Conclusion: This community service activity with presentations, simulations, and role-plays successfully strengthened the skills (PPGD) for nursing and midwifery students. Suggestions for the future are able to facilitate the continuation of routine and sustainable training sessions by expanding its scope, involving non-health students, the community, and Posyandu cadres.